THE PROBLEM OF WORKING ON A STILL LIFE COMPOSITION MADE OF DIFFERENT COLORED OBJECTS ON A CONTRASTING BACKGROUND - Jabbarov Botirsher Gulomovich (Web of Journals Publishing, 2024)
This article talks about the rules of creating a composition from different colored objects in painting, which is the main specialty of higher educational institutions specializing in fine arts, and the specific aspects of its work on a contrast background are analyzed.
Keywords: still life, frontal, volumetric, deep-spatial composition, laws of composition, rules, styles, tools, contrasting objects, chromatic colors, warm and cold colored objects, solid background, linear and aerial perspective, harmony, integrity, spatiality.